Oxidative Stress in the Blood Labyrinthine Barrier in the Macula Utricle of Meniere’s Disease Patients - Ishiyama, Gail; Wester, Jacob; Lopez, Ivan A.; Beltran-Parrazal, Luis; Ishiyama, Akira (Frontiers in Physiology, 2018)
The blood labyrinthine barrier (BLB) is critical in the maintenance of inner ear ionic and fluid homeostasis. Recent studies using imaging and histopathology demonstrate loss of integrity of the BLB in the affected inner ear of Meniere’s disease (MD) patients. We hypothesized that oxidative stress is involved in the pathogenesis of BLB degeneration, and to date there are no studies of oxidative stress proteins in the human BLB. We investigated the ultrastructural and immunohistochemical changes of the BLB in the vestibular endorgan, the macula utricle, from patients with MD (n = 10), acoustic neuroma (AN) (n = 6) and normative autopsy specimens (n = 3) with no inner ear disease. Each subject had a well-documented clinical history and audiovestibular testing. Utricular maculae were studied using light and transmission electron microscopy and double labeling immunofluorescence. Vascular endothelial cells (VECs) were identified using isolectin B4 (IB4) and glucose-transporter-1 (GLUT-1). Pericytes were identified using alpha smooth muscle actin (αSMA) and phalloidin. IB4 staining of VECS was consistently seen in both AN and normative. In contrast, IB4 was nearly undetectable in all MD specimens, consistent with the significant VEC damage confirmed on transmission electron microscopy. GLUT-1 was present in MD, AN, and normative. αSMA and phalloidin were expressed consistently in the BLB pericytes in normative, AN specimen, and Meniere’s specimens. Endothelial nitric oxide synthase (eNOS), inducible nitric oxide synthase (iNOS), and nitrotyrosine were used as markers of oxidative stress. The VECs of the BLB in Meniere’s had significantly higher levels of expression of iNOS and nitrotyrosine compared with normative and AN specimen. eNOS-IF staining showed similar patterns in normative and Meniere’s specimens. Microarray-based gene expression profiling confirmed upregulation of iNOS mRNA from the macula utricle of Meniere’s patients compared with AN. Nitrotyrosine, a marker recognized as a hallmark of inflammation, especially when seen in association with an upregulation of iNOS, was detected in the epithelial and stromal cells in addition to VECs in MD. Immunohistochemical and ultrastructural degenerative changes of the VEC suggest that these cells are the primary targets of oxidative stress, and pericyte pathology including degeneration and migration, likely also plays a role in the loss of integrity of the BLB and triggering of inflammatory pathways in MD. These studies advance our scientific understanding of oxidative stress in the human inner ear BLB and otopathology.